Community action planning for sustainable woodfuel production in Baringo and Kitui counties, Kenya - Wanjira, E.O.; Kitema, A.; Sola, P.; Muriuki, J.; Njenga, M. (CIFOR-ICRAF, 2022)
Community action plans (CAPs) offer a low-cost option to promote sustainable charcoal production. At a cost of around 13 USD per person per day, depending on the location, county governments could integrate CAP meetings into their activities. Training of Trainers (ToT) is another cost-effective approach to scaling knowledge on sustainable charcoal production. Building capacity among community trainers on the CAP process would enable charcoal producer associations (CPAs) to manage CAP meetings using their revenues from charcoal trade.